2011
DOI: 10.3109/08958378.2011.625995
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of crystalline silica-induced pulmonary toxicity revealed by global gene expression profiling

Abstract: A proper understanding of the mechanisms underlying crystalline silica-induced pulmonary toxicity has implications in the management and potential prevention of the adverse health effects associated with silica exposure including silicosis, cancer and several auto-immune diseases. Human lung type II epithelial cells and rat lungs exposed to crystalline silica were employed as experimental models to determine global gene expression changes in order to understand the molecular mechanisms underlying silica-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…These results were in line with our proteomic and cytotoxicity assay results. In agreement, a recent genomic study (using microarray) on the toxicity of MI reported that the particle perturbed the expression of genes in A549 cells that govern cellular growth and proliferation, cell death, inflammatory response and cell cycle (Sellamuthu et al ., ). More importantly, our gene expression analysis revealed a characteristic difference between CR and MI exposures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results were in line with our proteomic and cytotoxicity assay results. In agreement, a recent genomic study (using microarray) on the toxicity of MI reported that the particle perturbed the expression of genes in A549 cells that govern cellular growth and proliferation, cell death, inflammatory response and cell cycle (Sellamuthu et al ., ). More importantly, our gene expression analysis revealed a characteristic difference between CR and MI exposures.…”
Section: Discussionmentioning
confidence: 97%
“…For this purpose, a panel of 89 genes was selected for gene expression analysis (Supporting information Table S2). Some of these selected genes were known to be affected by silica particles in the literature (Sellamuthu et al, 2011), some were genes upstream and/or downstream of those proteins in the identified pathways based on the proteomic changes in the present study, and some were selected from unrelated pathways. Of the genes selected, 37 were found to exhibit altered expression following particle exposures (Supporting information Table S3).…”
Section: Gene Expression Changes In A549 Cells Exposed To Silica Partmentioning
confidence: 99%
“…To evaluate the harm to cells by inhalable mineral granules which constitute the bulk of the granules, are important factors that should not be ignored. Scientifically objective evaluation of the components of inhalable mineral granules that pose a danger to cells could provide the basis for developing standards to detect and reduce it in the environment (Zhang et al, 2005;Sellamuthu et al, 2011;Maisanaba et al, 2014 …”
Section: Introductionmentioning
confidence: 99%
“…Silicosis, an irreversible and incurable disease, is the most consequential adverse health effect associated with silica exposure. To understand the underlying mechanisms of silicosis, global gene expression profiling by employing microarray, or newer sequencing platforms, and bioinformatic analysis of gene expression data were utilized 15 , 16 , 17 . However, there are still some missing gaps in this aspect.…”
Section: Discussionmentioning
confidence: 99%